A new model to evaluate the long-term cost effectiveness of orphan and highly specialised drugs following listing on the Australian Pharmaceutical Benefits Scheme: The Bosentan Patient Registry - Owen, A.; Spinks, J.; Meehan, A.; Robb, T.; Hardy, M.; Kwasha, D.; Wlodarczyk, J.; Reid, Christopher (2008)
Backgound: Pharmaceutical subsidy schemes are under increasing pressure to evaluate the cost effectiveness of new highly specialised and orphan drugs for universal subsidy. In the absence of longer-term outcome data, drug sponsors often present modelled data, which can carry a significant level of uncertainty over longer-term projections. Risk-sharing schemes between drug sponsor and government may provide an acceptable method of balancing the uncertainty of longer-term cost effectiveness with the public demand for equitable and timely access to new drugs. Methods: The Bosentan Patient Registry (BPR) is an example of a unique risk-sharing model utilised in Australia aiming to provide clinical evidence to support the modelled predictions, with the registry survival outcomes linked to future price. Concomitant medication, health and vital status data was collected from clinicians, government health departments and death registries. Results: The BPR has identified a number of issues surrounding registry governance, ethics and patient privacy, and the collection of timely and accurate data, which need to be addressed for the development of a generic registry model for systematic evaluation. Conclusion: The success of a generic drug registry model based on the BPR will be enhanced by addressing a number of operational issues identified during the implementation of this project. © 2008 Informa UK Ltd.